A study of dendritic ionic liquid crystals: Using (S)-4-citronellyloxybenzoic acid and polypropylene imine dendrimers - Turkcu, Harun Nezih; Ocak, Hale; Gurbuz, Mustafa U.; Cakar, Fatih; Bilgin-Eran, Belkiz; Tulu, Metin (ELSEVIER SCIENCE BV, 2016)
In order to investigate the relationship between macromolecular structures and mesomorphic properties; dendritic ionic liquid crystals have been synthesized either by conventional method or microwave assisted synthesis technique and characterized by spectroscopic methods (FT-IR, H-1-NMR, C-13-NMR). Polypropylene-imine (PPI) dendrimers based on diaminobutane (DAB) having increasing number of amino terminal groups (DABn; n = 4, 8,16,32) were interacted with (S)-4-citronellyloxybenzoic acid (S-CBA) which already possessed liquid crystal property. These interactions were accomplished either by sonification to obtain quaternary ammonium salt or covalently linked by using appropriate coupling reagent. The liquid crystalline properties of the dendritic molecules were investigated by differential scanning calorimetry (DSC) and polarizing optical microscopy (POM). Thermal stability was studied by Thermal Gravimetric Analysis (TGA). Synthesized ion complexes showed a non-tilted smectic mesophase with wider mesomorphic range than that of single mesogenic unit, whereas those derivatives generated by covalent linkage exhibited no mesomorphism. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Liquid crystalline dendrimer; PPI; Smectic mesophase; HYPERBRANCHED POLYMERS; CARBOXYLIC-ACID; MESOMORPHISM; PROTONATION; COMPLEXES; Chemistry; Physics